The Role of Islamic Guidance and Counseling in Strengthening the Faith and Spirituality of the Community in Aek Nabara, Labuhan Batu - Hasan Hamzah Lubis; Fakhrurrozi Fakhrurrozi; Muhammad Sapii Harahap (FKIP - Universitas Riau, 2026)
This study aims to determine the role of Islamic counseling in strengthening the faith and spirituality of the community in Aek Nabara, Labuhan Batu Regency, and to identify supporting and inhibiting factors in its implementation. This study used a descriptive qualitative method with a field study approach. Data collection techniques included interviews, observation, and documentation with Islamic counselors, community leaders, and the assisted community. The results indicate that Islamic counseling plays a significant role in enhancing community spirituality. This is evident in increased awareness of worship, particularly congregational prayer, an improved understanding of Islamic faith, and an increase in religious activities such as religious study groups and religious study groups. Furthermore, there has been an increase in moral awareness, more harmonious social relations, and community social awareness. Supporting factors include support from religious leaders, the local government, community enthusiasm, and the active role of religious counselors. Inhibiting factors include community busyness, limited number of counselors, low religious understanding among some, and the influence of modernization. In conclusion, Islamic counseling plays a strategic role in strengthening faith and enhancing community spirituality in Aek Nabara, Labuhan Batu Regency.